BELGIAN REFUGEES IN PEMBROKESHIRE DURING THE FIRST WORLD WAR. (1st June 2021) - Hancock, Simon
The experiences of Belgian refugees during the First World War remain a comparatively neglected area of research. This article examines the experiences of Belgian refugees in Pembrokeshire, the largest concentration in Wales. It considers responses to the newcomers, the formation and activities of refugee committees, the impact of the Defence of the Realm Act on refugees, their patterns of employment (especially fishing), the provisions made for the refugees' education and religion, as well as occasional tensions between the local community and the visitors. It concludes with a discussion of the refugees' return to Belgium at the end of the war.